Farming or Foraging?: Household Labour and Livelihood Strategies amongst Smallholder Cocoa Growers in Papua New Guinea - Curry, George; Koczberski, Gina; Omuru, E.; Nailina, R. (2007)
Drawing on household level studies of cocoa production amongst village communities in Papua New Guinea’s Gazelle Peninsula, Farming or Foraging? presents a socio-economic and cultural model of smallholder productivity. The book discusses how commercial sector organisations can be drawn upon to provide smallholder extension strategies that are better integrated with the livelihoods of village producers. This book will be of value to researchers and agricultural extension organisations working with smallholders in developing countries across a range of different cash crops.